Optimization of Friction Stir Welding Process Parameters of Dissimilar AA2024-T3 and AA7075-T73 Aluminum Alloys by Using Taguchi Method - Abbass, Muna K.; Al-Kubaisy, Munthir M.; Abdulkadhim, Ruqaya (Al-Khwarizmi Engineering Journal, 2017)
The aim of present study is to determine the optimum parameters of friction stir welding process and known the most important parameter along with percentage contribution of each parameter which effect on tensile strength and joint efficiency of FS welded joint of dissimilar aluminum alloys AA2024-T3 and AA7075-T73 of 3 mm thick plates by applied specific number of experiments using Taguchi method .AA2024 was placed on the advancing side and AA7075 on the retreating side. FSW was achieved under three different rotation speeds (898, 1200 and 1710) rpm, three different welding speeds (20, 45 and 69) mm, three different pin profiles (cylindrical, threaded cylindrical and cone) and tool tilt angle 2◦. Taguchi method was proposed the orthogonal array of L9 based on the three number of process parameters and the three levels of variation for each parameter , Sratio and ANOVA analysis of robust design were applied to the results. The result of Sratio analysis were obtained to find the parameters optimization, which has been of rotation speed equal to 898 rpm, welding speed 45 mm, and threaded cylindrical pin profile with joint efficiency (76%). The tensile strength result shows that the welding speed was the most important parameter with a percentage contribution of 66.05 % over the other process parameters.